2010
DOI: 10.1136/qshc.2009.036871
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a set of interventions to reduce interruptions and distractions to nurses during medication administration

Abstract: Objective To assess the impact of a set of interventions in reducing the interruption/distraction rate during medication administration. Design and participants Pre-and postintervention observational study of nurses undertaking medication rounds. Setting Acute Medical Admissions Unit (AMAU) of a 1000-bed teaching hospital. Intervention A set of measures previously proven successful in reducing interruptions (behaviour modification and staff education; checklists; visible symbols in the form of a red vest; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(149 citation statements)
references
References 18 publications
9
138
1
1
Order By: Relevance
“…This study was in line with (Camiré, Moyen and Stefox, 2009) who reported that improved medication safety can be achieved by optimizing the safety of the medication process, eliminating situational risk factors. Furthermore, (Relihan et al, 2010) discovered that patients' education about the importance of medication administration and the meaning of the nurse's red vest important in reducing medication errors and interruption (Relihan et al, 2010).In addition (Mohamed and Gabar, 2010) suggested orientation and training new nurses, maintain adequate number of nurses on each shift, as well as conducting close supervision during medication administration.…”
Section: Discussionmentioning
confidence: 99%
“…This study was in line with (Camiré, Moyen and Stefox, 2009) who reported that improved medication safety can be achieved by optimizing the safety of the medication process, eliminating situational risk factors. Furthermore, (Relihan et al, 2010) discovered that patients' education about the importance of medication administration and the meaning of the nurse's red vest important in reducing medication errors and interruption (Relihan et al, 2010).In addition (Mohamed and Gabar, 2010) suggested orientation and training new nurses, maintain adequate number of nurses on each shift, as well as conducting close supervision during medication administration.…”
Section: Discussionmentioning
confidence: 99%
“…Literature Review Most of the studies aiming at determining interruptions during the medication administration have recently been carried out (6). The interruption rates found in these studies which were conducted in different countries were close to one another.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we analysed if negative effects of the interruption are avoided if the user's performance increases having a complete and uninterrupted interaction. Comparing our research with other research [46,47] that used avoidance of interruption techniques, none were seen to use fuzzy perceptions and did not consider users' uncertainty, which increases the error degree to avoid interruption.…”
Section: Interruption Factor Recoverymentioning
confidence: 71%